Visible Spectroscopic Estimation and Validation of Cefpodoxime Proxetil in Bulk and Pharmaceutical Dosage Forms - SREEKANTH, N.; BABURAO, CH.; RAMALINGAM, P.; GANAPATY, S. (Asian Journal of Chemistry, 2010)
A simple, sensitive, accurate visible spectroscopic method has been developed for the quantitative estimation of cefpodoxime proxetil in bulk and pharmaceutical dosage forms. The method was mainly based on the formation of green colour chromogen with potassium dichromate in acidic condition or medium. The produced colour was measured at wavelength maximum of 570 nm against reagent blank. The proposed method was showing linearity in the concentration range of 1-5 μg/mL.The developed method was validated statistically for its linearity, accuracy and precision as per FDA guidelines.